Symplocos huythacae (Symplocaceae), a new species from the Colombian Cordillera Oriental - Varón-Castañeda, Alejandro; Venegas-Carreño, Juan Simón; Jara-Muñoz, Orlando Adolfo (Phytotaxa, 2025)
Here, we describe a new species of Symplocos from Colombia distinguished by a characteristic abaxial leaf indument, sericeous buds and small corollas 4.0–5.6 mm in length. A description of pollen of this species is provided, along with photographs of the living specimen showing its habit and reproductive structures. Additionally, a preliminary conservation status evaluation is presented.